2016
DOI: 10.1177/2047487316664147
|View full text |Cite
|
Sign up to set email alerts
|

The blood pressure-lowering effect of a single bout of resistance exercise: A systematic review and meta-analysis of randomised controlled trials

Abstract: A single bout of resistance exercise can have a BP-lowering effect that last for up to 24 hours. Supine recovery and the use of larger muscle groups resulted in greater BP reductions after resistance exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
3
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 62 publications
6
105
3
12
Order By: Relevance
“…Divergences of results seem to be related to the characteristics of samples studied, mainly in relation to pre-experiment BP values. Higher reduction magnitudes appear to occur in individuals with higher BP values and untrained individuals [28][29] . Gerage et al 19 submitted 29 normotensive and untrained older women to 12 weeks of RT in three weekly sessions and observed reductions in SBP (-5 mmHg).…”
Section: Discussionmentioning
confidence: 92%
“…Divergences of results seem to be related to the characteristics of samples studied, mainly in relation to pre-experiment BP values. Higher reduction magnitudes appear to occur in individuals with higher BP values and untrained individuals [28][29] . Gerage et al 19 submitted 29 normotensive and untrained older women to 12 weeks of RT in three weekly sessions and observed reductions in SBP (-5 mmHg).…”
Section: Discussionmentioning
confidence: 92%
“…Post-exercise hypotension (PEH) has been observed in normotensive and hypertensive humans 8,9 , likewise, in animal models of hypertension 7 , being greater in hypertensive than normotensive subjects 24,25,26 . In humans, PEH has been documented following various types of dynamic exercise (walking, running, cycling, and swimming), as well as in resistance exercise 7,25,26,27,28 .…”
Section: Post-exercise Hypotensionmentioning
confidence: 99%
“…Different methods have been used to assess it, such as the auscultatory method 31,32 , intra-arterial measurement method 33,34 , and ambulatory blood pressure monitoring (24h assessment) 29,30,31,35 . In the recent meta-analysis, Cassonatto et al 8 showed that a single bout of resistance exercise elicited small-to-moderate reductions in systolic blood pressure at 60 and 90 minutes after exercise, and in 24-hour ambulatory blood pressure compared to control session. They concluded that a single bout of resistance exercise could have a blood pressure-lowering effect that lasts up to 24 hours.…”
Section: Post-exercise Hypotensionmentioning
confidence: 99%
See 2 more Smart Citations